The role of microglia in the pathogenesis of Azheimer's disease - LYU Langman, CHEN Shaoxiang (Jichu yixue yu linchuang)
Alzheimer's disease (AD) is the most common neurodegenerative disease. Microglia are inherent immune cells in the central nervous system, regulating and monitoring the stability of the surrounding environment. After activation, microglia have limited effects and can phagocytose part Aβ,However,Aβ Increased levels of microglia can induce chronic neuroinflammatory responses, leading to neurotoxicity and affecting the course of Alzheimer's disease. The role of microglia in neuroinflammatory response and the pathogenesis of Alzheimer's disease can not be ignored. This study aims to explore the potential target of microglia and provide a new entry point for the pathogenesis and clinical treatment of Alzheimer's disease.